PRESTASI KERJA: AKTUALISASI DIRI, PENGHARGAAN, DAN KEBUTUHAN SOSIAL - Syahfauzi, Kevin; Nurwanti, Nurwanti (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
The purpose of this study was to find out the effect of Self Actualization, Esteem, andSocial Belongingness on the Work Performance. The sample used in the study was 62 employees using purposive sampling techniques. Where the techniques and data are done using a questionnaire, while the analysis is done using multiple regression. The results of the study indicate that Self Actualization, Esteem and Social Belongingness affect the Work Performance. Therefore, company needs to pay attention to Self Actualization, Esteem and Social Needs in the workplace to obtain employee’s work achievement expected from the company.